NEW HALOTIN (IV) WITH EDTA: SYNTHESIS AND INFRARED STUDY - SERIGNE CISSE; IBRAHIMA CISSE; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Tri acidic or neutral ethylenediaminetetraacetato [H3Y- or Y4-] containing adducts and derivatives have been synthesized and studied by infrared. The suggested structures are discrete with octahedral environments around the tin centres, the thylenediaminetetraacetic anion behaving as a tridentate, pentachelating and bidentate, pentachelating and tridentate ligand. For the last structure when intermolecular hydrogen bonds involving OH group are considered, a supramolecular architecture may be obtained.